IDENTIFIKASI ATRIBUT STRATEGI EMPLOYER BRAND EQUITY DALAM MENARIK KARYAWAN BERTALENTA BERDASARKAN GENDER DAN PENGALAMAN KERJA - Miradewi, Santi; Fitriani, Risma (2021)
Recently, employer branding has been used in the field of human resources in companies to attract better employees. This study aims to analyze the attributes that influence employer brand equity strategies in attracting talented employees, using a quantitative approach. The object of this research is the scholarship recipient students studying in Karawang district. Gender and experience differences are also studied because they can have different influences and can be a consideration for human resource managers to understand the theoretical foundation of work brands and their application in practice. There are 23 research attributes which are classified into 6 consisting of social values, market values, economic values, application values, and work environment. 98 respondents rated them as scholarship recipients in Karawang. Data analysis used the Independent T Test with the SPSS 20 program. The results showed that the male respondents' enthusiasm was higher for the attractiveness attribute of the employer than the female respondents. Meanwhile, based on experience, respondents who have work experience are higher on the attractiveness attribute of the employer than respondents who do not have work experience.